Simultaneous determination of 3-hydroxypropionic acid, methylmalonic acid and methylcitric acid in dried blood spots: Second-tier LC-MS/MS assay for newborn screening of propionic acidemia, methylmalonic acidemias and combined remethylation disorders - Monostori, Péter; Klinke, Glynis; Richter, Sylvia; Kölker, Stefan; Hoffmann, Georg F.; Gramer, Gwendolyn; Okun, Jürgen G. (PLOS ONE, 2017)
Background and aims Increased propionylcarnitine levels in newborn screening are indicative for a group of potentially severe disorders including propionic acidemia (PA), methylmalonic acidemias and combined remethylation disorders (MMACBL). This alteration is relatively non-specific, resulting in the necessity of confirmation and differential diagnosis in subsequent tests. Thus, we aimed to develop a multiplex approach for concurrent determination of 3-hydroxypropionic acid, methylmalonic acid and methylcitric acid from the same dried blood spot (DBS) as in primary screening (second-tier test). We also set out to validate the method using newborn and follow-up samples of patients with confirmed PA or MMACBL. Methods The assay was developed using liquid chromatography-tandem mass spectrometry and clinically validated with retrospective analysis of DBS samples from PA or MMACBL patients. Results Reliable determination of all three analytes in DBSs was achieved following simple and fast (<20 min) sample preparation without laborious derivatization or any additional pipetting steps. The method clearly distinguished the pathological and normal samples and differentiated between PA and MMACBL in all stored newborn specimens. Methylcitric acid was elevated in all PA samples; 3-hydroxypropionic acid was also high in most cases. Methylmalonic acid was increased in all MMACBL specimens; mostly together with methylcitric acid. Conclusions A liquid chromatography-tandem mass spectrometry assay allowing simultaneous determination of the biomarkers 3-hydroxypropionic acid, methylmalonic acid and methylcitric acid in DBSs has been developed. The assay can use the same specimen as in primary screening (second-tier test) which may reduce the need for repeated blood sampling. The presented preliminary findings suggest that this method can reliably differentiate patients with PA and MMACBL in newborn screening. The validated assay is being evaluated prospectively in a pilot project for extension of the German newborn screening panel (‟Newborn screening 2020”; Newborn Screening Center, University Hospital Heidelberg).
Gesehen am 26.04.2018